TRADITIONAL MEDICINAL PRACTICES AND PRACTITIONERS OF THE TAI KHAMTIS OF NARAYANPUR, ASSAM - Saikia, Parishmita; Gogoi, Thagiram (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Tai Khamtis have inherited traditional medicinal knowledge passed over generations. People from faraway places visit the Khamti healers for certain cures. This valuable ancient knowledge is based on the use of locally available resources and cost – effective and natural skills. The present study observes the different techniques and methods of treatment in Khamti medicine as well as the role of the traditional practitioners of Khamti medicine. This traditional medicinal knowledge is an integral part of the Tai Khamti community. Over the years, varied factors have influenced the overall functioning of the traditional medicinal system. The study tries to understand this nature of changes in the system and the major factors responsible for such deviations.